A Fused Cuk-Sepic Converter Topology For Solar/Wind Hybrid Standalone System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electricity Derived From Renewable Energy Sources Are Unpredictable And Intermittent In Nature. Continuous Power Supply Is A Challenging Task, Obtained By Maximum Utilization Of Two Or More Resources Resulting In Hybrid System. This Work Proposes A Fused Converter Topology For A Hybrid Solar/Wind System Extracting Maximum Power. The Hybrid Configuration Permits The Sources To Feed The Load Individually Or Simultaneously Based On Its Availability. The Proposed Converter Is The Integration Of Cuk And Sepic Converter. The Characteristic Feature Of Fused Cuk-Sepic Converter Is That It Removes The High Frequency Harmonics. Simulation Is Done Using Matlab/Simulink And An Ac Output Of 300v, 10a Is Obtained. Hardware Implementation Is Done To Validate The Performance Of The Proposed Cuk-Sepic Converter